RESEARCH STUDY OF THE EFFECT OF VARIATION OF CEMENT WATER FACTOR IN BREACH WATER CONCRETE FACTING USING ADMIXTURE ON THE COMPRESSIVE STRENGTH OF CONCRETE - Farizal, Teuku; Basrin, Defry; Samsunan; Febrianti, Dian; Amin, M. Arrie Rafshanjani (RADJA PUBLIKA, 2023)
Admixture is an additional ingredient in concrete that is added when mixing concrete takes place in the hope of changing the properties of concrete to make it more suitable for a particular job. In this study, the material used was Sikacrete W with a percentage of 0%, 13% and 16% by weight of cement. The specimens used were cylinders (15 x 30) cm of 12 specimens for each FAS. FAS variations in this study included 0.35, 0.40 and 0.50 with a test age of 28 days. The results of this study, for FAS 0.35 the average concrete compressive strength for STATPLA was 280.24 kg/cm2, STATPDA was 110.38 kg/cm2, SDATPDA (13%) was 244.00 kg/cm2 and SDATPDA (16%) was 256.89 kg/cm2. FAS 0.40 average concrete compressive strength for STATPLA is 272.09 kg/cm2, STATPDA is 94.37 kg/cm2, SDATPDA (13%) was 237.18 kg/cm2 and SDATPDA (16%) was 249.18 kg/cm2. FAS 0.50 average concrete compressive strength for STATPLA was 238.83 kg/cm2, STATPDA was 74.05 kg/cm2, SDATPDA (13%) was 192.22 kg/cm2 and SDATPDA (16%) was 202.23 kg/cm2. These results indicate that there is an influence on FAS variations in concrete casting in brackish water with the addition of admixture.